Examining X-ray Sources in Trumpler 14 and 16 - Bilty, Kati (My University, 2010)
We have obtained X-ray data from the orbiting Chandra X-ray observatory in order to investigate the hot stars in the star clusters Trumpler 14 and 16. Our data set contains a number of CCD images centered on two stars in the clusters (HD93250 and HD93129). After combining our images into a master image we determined the X-ray sources and identified them with previously cataloged optical sources. Spectra, which relate to the X-ray temperature of a star?s wind, were created for the brightest sources.
Color poster with text and images.
Keywords: Early stars--Spectra; Spectral irradiance--Measurement; X-ray spectroscopy; Posters